The green transformation of agricultural production: evaluating the spatial role of agricultural industrial structure innovation in Guangdong, China - Zhang, Weikun; Li, Zheng; Wagan, Shoaib Ahmed; Tan, Shiwei (Frontiers in Sustainable Food Systems, 2024)
The primary function and spatial layout of agriculture are essential foundations and prerequisites for achieving green development. This paper explores the growth drivers for the green transformation of agricultural production in Guangdong, China, aiming to guide the continuous green and low-carbon development of agricultural productivity in Guangdong. Based on the panel data of 21 prefecturelevel cities in Guangdong, China, from 2004 to 2022, this paper uses DEA-BCC and DEA-Malmquist to measure the agricultural green total factor productivity (AGTFP) and its decomposition efficiency in Guangdong China. The SDM is employed to analyze its spatial spillover roles of the agricultural industrial structure (AIS) innovation. The results show that the AGTFP varies with an overall fluctuating upward trend, but the imbalance of regional differences still exists, characterized as "Pearl River Delta > Eastern Wing > Western Wing > Mountainous Area," indicating the siphoning role from Pearl River Delta. There is a strong spatial correlation between the AGTFP and the AIS. Our evidence suggests that the AIS innovation improves the AGTFP and can have positive spatial consequences in neighboring areas. Besides, human capital hinders AGTFP, accounting for the self-exploitation in agricultural production driven by the excessive labor force input. Our findings highlight the spatial impact of the AIS innovation on the AGTFP when greening agricultural production.